A comprehensive review of thermo-physical properties and convective heat transfer to nanofluids. (September 2015) - Solangi, K.H.; Kazi, S.N.; Luhur, M.R.; Badarudin, A.; Amiri, A.; Sadri, Rad; Zubir, M.N.M.; Gharehkhani, Samira; Teng, K.H.
Abstract: Nanofluids are fluid nanoparticle suspensions that exhibit enhanced properties at modest nanoparticle concentrations. Nanofluids have unique heat transfer properties and are utilized in high heat flux systems (e.g., electronic cooling systems, heat exchanger liquids, solar collectors, and nuclear reactors). However, suspension stability is critical in the development and application of these heat transfer fluids. Reynolds number, mass concentration, and particle size control the heat transfer behavior of fluids. Sedimentation and agglomeration of nanoparticles in nanofluids and their dispersion have rarely been investigated. Therefore, this paper explains the parameters that affect the stability of nanofluids and the different techniques used to evaluate the stability of nanofluids. This paper also presents an updated review of properties of nanofluids, such as physical (thermal conductivity) and rheological properties, with emphasis on their heat transfer enhancement characteristics. Studies on zeta potential as a function of pH are discussed and extended further to identify opportunities for future research. Highlights: Comprehensive review of nanofluids and latest methods of preparation. Parameters that affect the stability of nanofluids and the different techniques are discussed. Effect of different surfactants on the rheological properties of nanofluids has been presented. Sedimentation and agglomeration of nanoparticles in nanofluids are discussed in detail. zeta potential as a function of pH is discussed and opportunities for future research.